Wertschöpfungsnetzwerke in Zeiten von Infektionskrisen - Stich, Volker; Schröer, Tobias; Linnartz, Maria; Marek, Svenja; Herkenrath, Clara; Hocken, Christian; Kaufmann, Jonas (Forschungsbeirat der Plattform Industrie 4.0 / acatech – Deutsche Akademie der Technikwissenschaften, 2021)
Als Beispiel einer globalen Krisensituation zeigt die COVID-19-Pandemie eindrucksvoll die Schwachstellen heutiger Wertschöpfungsnetzwerke. Vor dem Hintergrund zunehmend komplexer und vernetzter Wertschöpfungsnetzwerke steigt für Unternehmen die Bedeutung einer resilienten Gestaltung derselben. Dabei wird davon ausgegangen, dass ähnliche Krisensituationen in Zukunft häufiger auftreten werden. Ziel dieser Expertise ist es, Unternehmen bei der Identifikation von Potenzialen und Maßnahmen für die resiliente Gestaltung ihrer Wertschöpfungsnetzwerke zu unterstützen.

The COVID-19 pandemic has demonstrated the far-reaching consequences companies and entire value networks face in time of an infection crisis. In its latest expert report, the Research Council of the Plattform Industrie 4.0 has analysed precisely these challenges and identifies strategies and drivers for building resilient value networks. Key resilience strategies are robustness and agility, which are driven by anticipation and preparation and transparency and speed, respectively. Fields of action to implement these strategies are network design, data integration, and Industrie 4.0 Technologies. Network design can be made more resilient by expanding collaboration with network partners and analysing – and increasing – the resilience of suppliers as well while data integration will greatly benefit from a standardisation of data exchange protocols between value partners within the network. The Research Council further proposes several action recommendations for Industrie 4.0 Technologies. Given that Industrie 4.0 Technologies support the accessibility and availability of data and use these data to generate new insights, it is recommendable to implement big data analytics and utilise both Artificial Intelligence and digital twins or digital shadows as these technologies improve end-to-end transparency and responsiveness. At the same time, they also allow companies to retain their ability to act by facilitating the potential of Smart Hardware and Advanced Robotics. These strategies are described in greater detail in the expert report, along an overview of further response tactics and action recommendations in order to increase the resilience of value networks in times of infection crises.
Value Networks in Times of Infection Crises
Keywords: FOS: Economics and business; FOS: Other engineering and technologies